Relação do comer intuitivo e da restrição alimentar com o estado nutricional de universitárias da Região Sul do Brasil - Majolo, Tamara Goldstein Chazan (2020)
Losing weight for health or aesthetic purposes regardless of the Body Mass Index (BMI) of the individual is a common and frequent desire, especially among the female population. Studies point out that the traditional methods used in food restriction are not sustainable in the long run: most people recover all the weight they have lost or even put on more weight. Dietary restriction may be a risk factor for eating disorders, disordered eating, obesity, nutritional deficiencies, depressive symptoms, increased anxiety, social isolation, poor body image and self-esteem. Alternatively, Intuitive Eating, an approach created by two American nutritionists (Evelyn Tribole and Elyse Resch) has been growing in the scientific field, with the proposition that the individual feeds according to his hunger and satiety signs and not according to a prescribed diet. This study aims to evaluate the Intuitive Eating of the college students of the Southern Region of Brazil (Rio Grande do Sul, Santa Catarina and Paraná) and its relationship with the BMI through the Intuitive Eating Scale-2 (IES-2), a 23-item scale composed of four subscales: Unconditional Permission to Eat, Eating for Physical Rather than Emotional Reasons, Reliance on Hunger and Satiety Cues and Body-Food Choice Congruence. In the theoretical section, in book's chapter format, a survey of the scientific literature on the effects of dietary restriction and a detailed presentation of the Intuitive Eating was made. In the first article, presented in the empirical section, with a cross sectional design, a sociodemographic questionnaire, the IES-2 and the Restraint Scale in female students from Southern Brazil were applied via online form (qualtrics) to verify their relationship with BMI. This scale also has subscales: 1) Concern about dieting and 2) Weight fluctuation. The sample size calculation was 385, but the total number of participants was 1,012 students (ages 18 to 66 with an average age of 25.4). The results showed that eating intuitively can provide a lower BMI when analyzing all the BMI strata together. When they are analyzed by separate strata, there were variations (the higher the IES-2 score in eutrophy and overweigth, the higher the BMI; and in the obesity stratum, low, medium and high scores were found) suggesting important data for further research to expand the conclusions of this dissertation, contributing to better understand the complexity of eating behavior. In the second article, the evidence of the validity of IES-2 was evaluated, showing adequate factor loadings, presenting Cronbach's Alpha of 0.88 in the Eating for Physical rather than Emotional Reasons subscale; 0.86 in the Reliance on Hunger and Satiety Cues subscale; 0.86 in the Body-Food Choice Congruence subscale and 0.70 in the Unconditional Permission to Eat subscale as a good instrument to evaluate intuitive eating of Brazilian college students. Eating according to internal signs of hunger and satiety is related to lower BMI. However, when analyzing the BMI strata separately (eutrophy, overweight and obesity), this relationship is not confirmed. The data in this study show the importance of analyzing the peculiarity and characteristics of each BMI range, considering the complexity of the determinants that make up eating behavior.